Aesthetic Surgery in Patients with Lung Cancer: A Paradigm Shift. Issue 10 (October 2016) - Hidalgo, David A.; Baranski, Jan; Sinno, Sammy
Abstract : Background: Lung cancer is the most common cancer worldwide and the leading cause of cancer death. With the development of targeted therapy against causative driver mutations, some patients have experienced dramatic responses that have converted their disease into a chronic, stable form. Shifting concerns away from survival and back to quality-of-life issues has led some of these patients to seek aesthetic surgery. Methods: Three patient examples are presented to illustrate current lung cancer treatment modalities, disease responses, and subsequent experiences with aesthetic surgical procedures. Two patients presented for blepharoplasty and the third for revisional breast augmentation surgery. Results: Two patients were treated for lung cancer with targeted therapy and a third with more traditional chemotherapy before undergoing aesthetic surgery. All 3 patients experienced a normal recovery from surgery without any untoward results. Two remain free of disease and one has chronic stable disease. All have returned to normal, active lives. Conclusions: Recent developments in lung cancer treatment are transforming this entity into a less formidable diagnosis for some patients, much like breast cancer and prostate cancer. Plastic surgeons should be aware of this paradigm shift. Successfully treated patients should be considered as reasonable candidates for aesthetic surgery, particularly when they have the full support of their oncologist. Beyond the typical psychological benefits that plastic surgery can produce, it also provides affirmation in this patient population of a return to normalcy, thereby imparting hope and optimism for the future.